2018
DOI: 10.1111/imj.13935
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and fall risk associated with age‐related body composition changes; sarcopenia, obesity and sarcopenic obesity

Abstract: Sarcopenia, obesity and sarcopenic obesity are associated with many negative health outcomes, such as high fall risk and low health-related quality of life in geriatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
86
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 39 publications
5
86
1
2
Order By: Relevance
“…Although only a few previous studies portrayed the relation between quality of life and muscle strength, Ozturk et al showed that both gait speed and muscular strength were positively correlated in patients with sarcopenia. 29 However, in the current study, there was a negative correlation between SP and muscle strength, but no correlation with walking speed in BD patients.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Although only a few previous studies portrayed the relation between quality of life and muscle strength, Ozturk et al showed that both gait speed and muscular strength were positively correlated in patients with sarcopenia. 29 However, in the current study, there was a negative correlation between SP and muscle strength, but no correlation with walking speed in BD patients.…”
Section: Discussioncontrasting
confidence: 77%
“…Ozturk et al reported that the prevalence of sarcopenia was 21.8% in men and 8.7% in women. 29 In our study, the prevalence of Pre-SP, SP and severe SP in BD patients was 7.1%, 16.7% and 2.4% in men and 5.8%, 4.3% and 1.4% in women, respectively. However, the percentage of males in the sarcopenia group and the percentage of females in the non-sarcopenia group were statistically higher.…”
Section: Discussionsupporting
confidence: 48%
“…We evaluated SM exclusively by measurements of SM mass, and hand grip or walking speed will need to be evaluated for sarcopenia in future studies. The EWGSOP also suggested that sarcopenic patients experience a decreased QoL 22 . Previous studies have evaluated the association between sarcopenia and decreased QoL using the Short Form−36 or Euro‐QoL 5 Dimension 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…The EWGSOP also suggested that sarcopenic patients experience a decreased QoL 22 . Previous studies have evaluated the association between sarcopenia and decreased QoL using the Short Form−36 or Euro‐QoL 5 Dimension 22,23 . However, no studies have used the EPIC to evaluate urinary QoL in patients with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Body composition plays a pivotal and independent role in BP [58,61]. Although body composition is influenced by physical practice and diet habits [58], increased total fat, particularly abdominal fat, are key features of obese and aging [73]. The results of this study determined that overweight and obese middle-aged and older adults showed healthy values in trunk and total fat and in other proportionality parameters related with obesity [74,75] such as BMI, PI, biiliocristal/biacromial ratio, and WHR when having a high CRF.…”
Section: Discussionmentioning
confidence: 99%